Motivasi Belajar Mahasiswa Menggunakan Media Pembelajaran Google Classroom Pada Matakuliah Atletik Lanjutan - Jan Bobby Nesra Barus (UNIVERSITAS NEGERI MAKASSSAR, 2020)
ABSTRACTAs a result of the spread of Corona Virus Disease 2019 (Covid-19) in the world which has an impact on increasing the number of victims and property losses and has implications for broad socio-economic aspects in Indonesia. Referring to the Presidential Decree the Ministry of Culture and the Republic of Indonesia (Kemendikbud RI) launched a learning program from home, then all educational institutions which included the Quality Berastagi University changed face-to-face learning with online-based learning. The current situation requires all students to adapt to the learning process, learning system changes until the Covid-19 emergency period ends. Online-based learning is a solution for learning to continue as usual during the Covid-19 emergency, one of the online-based learning media used at the University of Quality Berastagi precisely in the Sports Education Study Program is google classroom. The purpose of this study was to determine the level of student motivation using the google classroom learning media in advanced athletics courses. Data collection techniques using test results and student learning motivation questionnaire. The population in this study were all students of the Sport Education Study Program FKIP Berastagi Quality University who took advanced athletics courses, then the sample used total sampling which meant that all students would be sampled as many as 21 students. The results showed that the level of student motivation to use google classroom at the Berastagi Quality University included in the high category (76,19%). ABSTRAKAkibat penyebaran Corona Virus Disease 2019 (Covid-19) di dunia yang telah berdampak meningkatnya jumlah korban dan kerugian harta benda serta menimbulkan implikasi pada aspek sosial ekonomi yang luas di Indonesia. Merujuk kepada Keppres tersebut Kementerian dan Kebudayaan Republik Indonesia (Kemendikbud RI) mencanangkan program belajar dari rumah, maka semua institusi pendidikan yang didalamnya termasuk Universitas Quality Berastagi merubah pembelajaran tatap muka dengan pembelajaran berbasis online. Situasi saat ini mengharuskan semua mahasiswa untuk beradaptasi mengikuti proses pembelajaran, perubahan sistem pembelajaran sampai masa darurat Covid-19 berakhir. Pembelajaran berbasis online merupakan sebuah solusi agar pembelajaran tetap berjalan seperti biasa selama masa darurat Covid-19, salah satu media pembelajaran berbasis online yang digunakan pada Universitas Quality Berastagi tepatnya pada Program Studi Pendidikan Olahraga adalah google classroom. Tujuan penelitian ini adalah untuk mengetahui tingkat motivasi mahasiswa menggunakan media pembelajaran google classroom pada matakuliah atletik lanjutan. Teknik pengumpulan data menggunakan tes hasil belajar dan angket motivasi belajar mahasiswa. Populasi pada penelitian ini adalah seluruh mahasiswa Program Studi Pendidikan Olahraga FKIP Universitas Quality Berastagi yang mengambil matakuliah atletik lanjutan, kemudian sampel mengunakan total sampling yang artinya seluruh mahasiswa akan dijadikan sampel penelitian sebanyak 21 mahasiswa. Hasil penelitian menunjukkan bahwa tingkat motivasi belajar mahasiswa dengan menggunakan google classroom di Universitas Quality Berastagi termasuk dalam kategori tinggi (76,19%).